TEACHER PERCEPTION ABOUT STUDENT BEHAVIOR, ENVIRONMENT CARE CULTURE ON THE CREATION OF HEALTHY SCHOOL - Asep Sunandar; Ediyanto Ediyanto; Mohd.Mokhtar Bin Tahar; Ade Dian Firdiana; Deni Hadiana (Pascasarjana UM, 2022)
The environment is a key factor in improving healthy full-day school activities. It has a direct impact on the creation of children’s learning enjoyment. The purposes of this research are to explore students' perspectives on Student Friendly Behavior, Environment Care Culture and their effects on the creation of Clean and Healthy schools. This research involved 242 Elementary School teachers as participants in the City of Malang. Data were collected through a questionnaire and analyzed employing the Path analysis technique. Results indicated that both student-friendly behavior and environmental care culture influenced the creation of healthy and clean schools. School leaders need to be a concern on this factor in building effective schooling systems. Other studies are suggested to focus on wider targets in order to gain more comprehensive findings on this environment factor